THE USE OF LITERATURE-BASED INSTRUCTION TO IMPROVE READING COMPREHENSION AND WRITING ACHIEVEMENTS OF THE EIGHTH GRADE STUDENTS - Ressy Novasyari (Faculty of Teacher Training and Education, Universitas Sriwijaya, 2019)
Abstract: This research aimed to investigate whether or not there were significant differences in reading comprehension and writing achievement between the eighth grade students of SMP Islam Az-Zahra 2 Palembang who were taught by using Literature-Based instruction and those who were not. This study used one of the quasi experimental designs: pretest-posttest design. The sample was selected purposively from the whole population based on their reading comprehension scores. Forty six eighth graders were selected as the sample and equally divided into experimental and control groups. Pretest and posttest were given to both groups. Using paired sample statistics, the results of the experimental group showed that the students’ reading comprehension and writing achievement ? significantly improved. Furthermore, the result of the independent t-test showed that with mean difference of reading comprehension was 8.609, t value 11.111(p<0.05). Moreover, the mean difference of writing achievement was 6.8043, t value 10.478 (p<0.05). Keywords: Literature-based instruction, reading comprehension and writing achievement.